Adversity, depressive symptoms and suicide attempts: study of women in community and comparison between women in prison and women in the community - Pinto, Vanessa Cristina Pires (2013)
Dissertação de mestrado integrado em Psicologia (área de especialização em Psicologia da Justiça)